An Analysis Figurative Language in Donald Trump’s Speech the 72nd Session of the United Nations General Assembly - Situmeang, Sindyana; Hilman, Evert Haryanto (Asosiasi Ide Bahasa Kepri, 2023)
The aim of this research is to analysis and describe the types of figurative language and translation strategy that were found in Donald Trump’s Speech. This research focuses on 3 types of figurative language. There are Symbolism, Euphemism and Antithesis. The types figurative meaning was found in Speech. In analysis the kinds of figurative language on Donald Trump Presidential Speech, the writer chooses on of Donald Trump’s Speech edition on 19 September 2017 in New York. To strengthen the analysis, the writer applied Descriptive research. By gathering relevant theories and data, descriptive study aims to characterize and elucidate the nonliteral meaning resulting from the use of figurative language. The data are analysis by selecting and classifying them into their types due to figurative language and translation strategy. From the result of this research the writer found 11 (eleven) type of figurative language which are symbolism, Euphemism, and Antithesis. The writer found 5 (five) Symbolism, 4 (four) Euphemism and 2 (two) Antithesis in Donald Trump’s Speech the 72nd Session of the United Nations General Assembly and the translation strategy uses is Semantic and Pragmatic strategies according to Chesterman Andrew (1997:85)